Analysing attitude as a determinant of counterfeit consumption among the Malaysian public sector employees - Abdul Shukor, Abdul Karim; Muda, Salwa; Idris, Asma’ Rashidah; Musman, Musliha; Hussin, Amariah Hanum (2023)
Counterfeiting, which encompasses the production, importation, exportation, distribution, and sale of counterfeit consumer goods that are intentionally designed and branded to resemble authentic products, is essentially a form of theft. It poses a major problem on a global scale as it can severely impact legitimate businesses by reducing sales, profits, brand trust, and overall value. The key factor influencing unethical behaviour, such as purchasing counterfeit goods, is individuals’ attitudes, which hold true regardless of the specific product category. The decision to engage in counterfeiting activities depends on whether individuals hold positive or negative attitudes towards such behaviour. While previous studies have examined various factors related to the demand for counterfeits, there has been limited research exploring the emotional aspects of consumer behaviour. Therefore, this study aims to investigate how attitudes influence counterfeit consumption. A quantitative approach was adopted to gather primary data, employing an online questionnaire survey completed by 363 public sector employees who participated in the study. The findings demonstrate a significant correlation between attitudes and counterfeit consumption. This research will contribute to the existing literature on counterfeit consumption, particularly in terms of understanding the impact of attitudes on consumer behaviour. Furthermore, the findings will provide valuable insights to policymakers, regulators, and industry stakeholders, aiding combatting counterfeiting.